Indian Journal of Chemistry- B - Indian National Science Academy; Council of Scientific & Industrial Research (India); National Institute of Science Communication and Information Resources (New Delhi, India) (New Delhi : Published by the Council of Scientific & Industrial Research in association with the Indian National Science Academy, 1976)
Print only.
Title from cover.
Keywords: Chemistry -- Periodicals; Chemistry, Organic -- Periodicals; Clinical chemistry -- Periodicals; Pharmaceutical chemistry -- Periodicals; Chemistry, Organic -- Periodicals; Biochemistry -- Periodicals; Chemistry; Chemistry, Organic; Clinical chemistry; Pharmaceutical chemistry